EVALUASI IMPLEMENTASI KEBIJAKAN TATA KELOLA KEPESERTAAN PBI DAERAH JAMINAN KESEHATAN NASIONAL DI KABUPATEN KAYONG UTARA DAN KABUPATEN KETAPANG PROVINSI KALIMANTAN BARAT - Dedet Triwahyudi; Firdaus Hafidz As Shidieq; Laksono Trisnantoro (Journal of Health Service Management, 2021)
Background: The management of the Regional Health Insurance was merged into BPJS Health after the implementation of the 2014 National Health Insurance program. Kayong Utara Regency and Ketapang Regency are part of the Regency that combines regional health insurance participation into BPJS Health. The implementation of regional PBI governance needs to be supported by adequate regulations, a strong stakeholder vision, communication between stakeholders that is in line with the policies of regional leaders. Objective: The general objective of this research was to explore the ability of stakeholders in implementing the governance of PBI participation in the National Health Insurance Region. Methods: This study used a realist evaluation approach with a descriptive case study design. The study used purposive sampling, the research subjects were 24 people. Data was collected by means of in-depth interviews and document review. Results: The implementation of the JKN Program is a strategic policy. North Kayong Regency insures the rich and the poor at BPJS Health, while Ketapang Regency only insures the poor or the poor. Based on the Context, Mechanism, and Outcome hypothesis, the management of PBI participants responded differently in the two districts. In the implementation of non-comprehensive regulatory influences, the Regional PBI Management had not been good in the two districts, a strategic vision that was not accompanied by a strategic plan and partial communication (mechanism) contributes to the results or in ensuring health insurance for the poor (outcomes). Conclusion: The government of Kayong Utara and Kabupaten Ketapang have a strong commitment to managing health insurance for the poor. The implementation of the Regional PBI in the two districts faces challenges in the form of regulations that are not yet comprehensive. Comprehensive regulations, clear targets, and cross-structure coordination are needed in the management of Regional PBI in North Kayong Regency and Ketapang Regency so that it can be carried out properly.